2024
DOI: 10.3390/brainsci14040392
|View full text |Cite
|
Sign up to set email alerts
|

The Necessity of Taking Culture and Context into Account When Studying the Relationship between Socioeconomic Status and Brain Development

Julie M. Schneider,
Mohammad Hossein Behboudi,
Mandy J. Maguire

Abstract: Decades of research has revealed a relationship between childhood socioeconomic status (SES) and brain development at the structural and functional levels. Of particular note is the distinction between income and maternal education, two highly correlated factors which seem to influence brain development through distinct pathways. Specifically, while a families’ income-to-needs ratio is linked with physiological stress and household chaos, caregiver education influences the day-to-day language environment a chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 227 publications
0
4
0
Order By: Relevance
“…While multigenerational homes can provide numerous communication partners, they may also lead to fewer one-on-one interactions. Research and intervention practices should therefore broaden the scope of language exposure to encompass input from primary caregivers as well as language exchanged among other family members such as siblings, aunts, uncles, and additional caregivers (Schneider, Behboudi & Maguire, 2024). Although the most frequent conversational partner for the majority of children is their mother, we found that caregivers reported that their children also interact often with a sibling, grandparent, father, uncle/aunt, friend, or teacher.…”
Section: Discussionmentioning
confidence: 83%
“…While multigenerational homes can provide numerous communication partners, they may also lead to fewer one-on-one interactions. Research and intervention practices should therefore broaden the scope of language exposure to encompass input from primary caregivers as well as language exchanged among other family members such as siblings, aunts, uncles, and additional caregivers (Schneider, Behboudi & Maguire, 2024). Although the most frequent conversational partner for the majority of children is their mother, we found that caregivers reported that their children also interact often with a sibling, grandparent, father, uncle/aunt, friend, or teacher.…”
Section: Discussionmentioning
confidence: 83%
“…Low educational attainment and migration background, especially when migration ensues from countries of lower SES, as utilised in this study, relate to social exclusion and marginalisation [ 9 , 129 ]. The underlying processes linking challenges to detrimental effects on child development may be differential, and family income seems of particular relevance [ 10 ]. Thus, integrating information on different aspects of family life is important.…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence, low educational background has been associated with limited strategies and knowledge about child development and child-rearing, both affecting secure attachment and healthy socioemotional development of the infant. Lower educational background is also being discussed in connection to reduced lexical richness and the grammar complexity of parents affecting children’s language abilities [ 10 ]. Disparities in parental education further contribute to differences in mental and physical health and relate to learning opportunities or academic expectations [ 6 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation